2009
DOI: 10.14429/dsj.59.1545
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver Nanoparticles using Facile Wet Chemical Route

Abstract: Stable aqueous monodispersed silver nanoparticles were synthesised by reducing silver nitrate using various sugars such as glucose, fructose, lactose, and sucrose at 55-60 o C. A mixture of two stabilising agents, polyvinyl pyrrolidone (PVP) of molecular weight (MW 40, 000) and gelatin plays a decisive part in controlling size and shape of superfine silver nanoparticles. Using PVP, better control of particle size was obtained, whereas a mixture of PVP, and gelatin resulted in sea urchin kind of structure. Effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 51 publications
(39 reference statements)
4
27
0
Order By: Relevance
“…We observed that a combination of high reductant volume, high temperature and high amount of NaOH resulted in abrupt color change for S-8 and S-20. This abrupt color change was also observed by Sahoo et al [18] Color change was observed to be slow …”
Section: Synthesis Of Silver Nanoparticlessupporting
confidence: 82%
“…We observed that a combination of high reductant volume, high temperature and high amount of NaOH resulted in abrupt color change for S-8 and S-20. This abrupt color change was also observed by Sahoo et al [18] Color change was observed to be slow …”
Section: Synthesis Of Silver Nanoparticlessupporting
confidence: 82%
“…Copper is easily reduced in solution using mild reductant such as ascorbic acid [29]. Addition of sodium hydroxide augmented the rate of reduction [30]. Copper is easily oxidized with a small amount of oxygen present [11].…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…Contrary to the alkali and NaBH 4 reduction method, where fast ion reducing processes hinder the effective protection of NPs [36], the use of a mild reducing agent, such as Na 2 CO 3 , and the uniform energy transfer from microwave radiation allow the formation of small and uniformly distributed Ni NPs [37]. The use of Na 2 CO 3 not only allows slow reduction for uniform nucleation but also gives a short time lag in reduction which, in turn, enhances the effective L-cysteine binding over Ni NPs, leading to high stability and narrow particle size distribution [38].…”
Section: Ftir Spectra Of Cyst-ni Npsmentioning
confidence: 99%